Materials Design and Applications II - Silva, Lucas F. M. da.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book highlights fundamental research on the design and application of engineering materials, and predominantly mechanical engineering applications. This area includes a wide range of technologies and materials, including metals, polymers, composites, and ceramics. Advanced applications include manufacturing cutting-edge materials, testing methods, and multi-scale experimental and computational aspects. The book introduces readers to a wealth of engineering applications in transport, civil, packaging and power generation.
1 The fundamental research on the design and application of engineering materials -- 2 The Predominantly mechanical engineering applications -- 3 A wide range of technologies and materials, including metals, polymers, composites, and ceramics -- 4 Advanced applications include manufacturing cutting-edge materials.
Keywords: Materials -- Analysis; Materials; Mechanics, Applied; Solids; Characterization and Analytical Technique; Materials Engineering; Solid Mechanics